Utilization of Labneh Whey Lactose Hydrolyzed Syrup in Baking and Confectionery - Wail-Alomari; Alsaed, Ali K.; Hadadin, Malik (Pakistan Journal of Nutrition, 2012)
Hydrolyzed labneh whey lactose syrup was obtained by the action of immobilized Beta-galactosidase enzyme using fluidized bed reactor system. The obtained sweet syrup was used as sugar replacement in three products (French - type bread, Cherry cake and Kunafah syrup). The sensory evaluation results showed that bread made with 25% sugar replacement level was better than the control one. For (Cherry cake and Kunafah) there were no significant differences between the products made with 25% sugar replacement level and the control samples. The bread dough mad with 25% sugar replacement had a better rheological properties with regards to stability, rate of absorption and mechanical tolerance indication. The nutritional value of the newly developed product was improved with regards to high amount of protein content compared to control products. No microbial growth was detected in both control and new developed bread products during storage.